2018
DOI: 10.1016/j.vph.2017.12.063
|View full text |Cite
|
Sign up to set email alerts
|

UDP-sugars activate P2Y 14 receptors to mediate vasoconstriction of the porcine coronary artery

Abstract: AimsUDP-sugars can act as extracellular signalling molecules, but relatively little is known about their cardiovascular actions. The P2Y14 receptor is a Gi/o-coupled receptor which is activated by UDP-glucose and related sugar nucleotides. In this study we sought to investigate whether P2Y14 receptors are functionally expressed in the porcine coronary artery using a selective P2Y14 receptor agonist, MRS2690, and a novel selective P2Y14 receptor antagonist, PPTN (4,7-disubstituted naphthoic acid derivative).Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…UDP-glucose fecal metabolite levels were positively associated with increased MAP in both SF and control rats, and fecal UDP-glucose levels were significantly lower in SF rats versus control rats during the recovery/rest period ( day 34 ). To our knowledge, no research has linked UDP-glucose and MAP outcomes, but UDP-glucose has been shown to produce porcine artery vasoconstriction through its action on P2Y 14 receptors ( 1 , 3 ). UDP-glucose’s vasoactive properties through cAMP-dependent signaling ( 3 ), and association with increased MAP suggests that this metabolite could be a promising target of future gut microbiota-linked hypertension research.…”
Section: Discussionmentioning
confidence: 99%
“…UDP-glucose fecal metabolite levels were positively associated with increased MAP in both SF and control rats, and fecal UDP-glucose levels were significantly lower in SF rats versus control rats during the recovery/rest period ( day 34 ). To our knowledge, no research has linked UDP-glucose and MAP outcomes, but UDP-glucose has been shown to produce porcine artery vasoconstriction through its action on P2Y 14 receptors ( 1 , 3 ). UDP-glucose’s vasoactive properties through cAMP-dependent signaling ( 3 ), and association with increased MAP suggests that this metabolite could be a promising target of future gut microbiota-linked hypertension research.…”
Section: Discussionmentioning
confidence: 99%
“…UDP and sugar derivatives such as UDP‐glucose and UDP‐galactose are G i ‐coupled P2Y 14 receptor agonists (Abbracchio et al, 2006, 2019; Carter et al, 2009). The analogues MRS2690 (diphosphoric acid 1‐α‐ d ‐glucopyranosyl ester 2‐[(4′‐methylthio)uridin‐5″‐yl] ester, 43 ), MRS2802 (α,β‐difluoromethylene‐UDP, 44 ), and MRS2905 (α,β‐methylene‐2‐thio‐UDP, 45 ) are much more potent agonists (Abbas et al, 2018; Carter et al, 2009; Das et al, 2010).…”
Section: Selective Ligand Tools To Study P2y Receptorsmentioning
confidence: 99%
“…For example, the P2Y14 receptors contribute to chemotaxis in human neutrophils [ 5 ]. Historically, the P2Y14 receptors were thought to be strictly uracil-diphosphate (UDP)-glucose-activated, while newer studies have suggested that UDP is also a potent agonist of these receptors [ 8 , 9 ]. At present, there is no evidence that the P2Y14 receptors are activated by ADP [ 51 ].…”
Section: Other P2y Receptors: P2y13 and P2y14mentioning
confidence: 99%
“…In turn, the P2Y13 receptor is mostly involved into cholesterol and glucose metabolism, bone homeostasis, pain transmission, and neuroprotection in central nervous system, whereas its role in platelet activation has not yet been established [ 6 , 7 ]. On the other hand, the P2Y14 receptor mediates vasoconstriction of the smooth muscle cells [ 9 ]. The P2Y1 and P2Y12 receptors are purinergic G protein-coupled receptors for ADP that are widely distributed within cells, including platelets [ 10 ].…”
Section: Introductionmentioning
confidence: 99%